AESTHETIC ISSUES OF SPEECH IN THE CONTEXT OF ADVERBIAL MODIFIER OF MANNER EXPRESSED IN AVETIK ISAHAKYAN’S POEM ―ABU-LALA MAHARI - Khachatryan, M. (SUSh Scientific Proceedings, 2025)
The issue of the interrelation between the national literary language and the writer’s individual language remains a constant subject of scholarly investigation. This is due to the necessity of both presenting the writer’s literary heritage in its entirety and evaluating the influence exerted by the writer on the development of the literary language. It is well known that great writers contribute equally to the creation of both literature and language. In this sense, Avetik Isahakyan is a great contributor, whose language attains the status of cultural value, grounded in one of its fundamental characteristics—its expressive power. The language of the poem under discussion exemplifies this quality: alongside its cognitive value, it also fulfills an aesthetic function, which is closely aligned with the poet’s intention—to exert an emotional impact on the reader. This is achieved through the combined presence of the merits of speech within the text. ―The merits of speech are embedded in the elements and components that constitute its content and form‖ [6, p. 380]. A literary theorist, discussing the aesthetic role of language in literary works, similarly notes: ―The finest literary works are distinguished by the diversity, flexibility, and harmony of their linguistic means‖ [7, pp. 219–220]. In this regard, the poem ―Abu-Lala Mahari‖ serves as an exemple. Its rich language is characterized by a remarkable diversity, freshness, and abundance of stylistic devices. The present study seeks to explore this through an analysis of adverbial modifiers of manner—the diverse manifestations of the adverbial modifier of manner—which the masterful poet employs to ensure the fundamental features of literary speech: imagery, precision, and variety. Through the effective realization of these features, he succeeds in solving the problem of aesthetic expression in language